Pro android 3 - Komatineni, Satya (Apress, 2011)
Pro Android 3 starts with the basics, giving you a firm foundation in Android development. It then builds on this foundation to teach you how to build real-world and fun mobile applications using the new Android 3.0 SDK. This book covers advanced concepts in detail including maps, geocoding, services, live folders, drag and drop, touchscreens, and the new Android 3.0 features: fragments and ActionBar. Pro Android 3 is uniquely comprehensive: it covers sensors, text to speech, OpenGL, live widgets, search, and the audio and video APIs. Using the code-heavy tutorials and expert advice, you'll quickly be able to build cool mobile apps and run them on dozens of Android-based smartphones. You'll explore and use the Android APIs, including those for media, sensors, and long-running services. And you'll check out what's new with Android 3.0, including the improved UI across all Android platforms, drag and drop, fragment dialogs, and more, giving you the knowledge to create stunning, cutting-edge apps, while keeping you agile enough to respond to changes in the future.